Evacuation During Hurricane Sandy: Data from a Rapid Community Assessment - Brown, Shakara (PLoS Curr, 2016)
Introduction: In anticipation of Hurricane Sandy in 2012 New York City officials issued mandatory evacuation orders for evacuation Zone A. However, only a small proportion of residents complied. Failure to comply with evacuation warnings can result in severe consequences including injury and death. To better ascertain why individuals failed to heed pre-emptive evacuation warnings for Hurricane Sandy we assessed factors that may have affected evacuation among residents in neighborhoods severely affected by the storm. Methods: Data from a mental health needs assessment survey conducted among adult residents in South Brooklyn, the Rockaways, and Staten Island from December 13-18, 2012 was assessed. Several disasters related questions were evaluated, and prevalence estimates of evacuation and evacuation timing by potential factors that may influence evacuation were estimated. Measures of association were assessed using chi-square and t-test. Results: Our sample consisted of 420 residents of which, only 49% evacuated at any time for Sandy. Evacuation was higher among those who witnessed trauma to others related to the World Trade Center attacks (66% vs. 40%, p=0.024). Those who reported extensive household damage after Sandy, had a higher rate of evacuation than those with minimal damage (83% vs. 30%, p<0.001). Among those who evacuated, evacuation before the storm was lower among residents living on higher floors (56% vs. 22%, p=0.022). Discussion: Given that warnings to evacuate were issued before Sandy made landfall, evacuation among residents in South Brooklyn, the Rockaways and Staten Island, while higher than the overall Zone A evacuation rate, was less than optimal. Continued research on evacuation behaviors is needed, particularly on how timing affects evacuation. A better understanding may help to reduce barriers, and improve evacuation compliance.